Inulin Derivatives Obtained Via Enhanced Microwave Synthesis for Nucleic Acid Based Drug Delivery - Sardo, Carla; Fabiola Craparo, Emanuela; Fiorica, Calogero; Giammona, Gaetano; Cavallaro, Gennara (Current Drug Targets, 2015)
A new class of therapeutic agents with a high potential for the treatment of different socially relevant human diseases is represented by Nucleic Acid Based Drugs (NABD), including small interfering RNAs (siRNA), decoy oligodeoxynucleotides (decoy ODN) and antisense oligonucleotides (ASOs). Although NABD can be engineered to be specifically directed against virtually any target, their susceptibility to nuclease degradation and the difficulty of delivery into target tissues severely limit their use in clinical practice and require the development of an appropriate nanostructured delivery system. For delivery of NABD, Inulin (Inu), a natural, water soluble and biocompatible polysaccharide, was derivatized by Spermine (Spm), a flexible molecule with four amine groups that, having pKa values in the range between 8-11, is mainly in the protonated form at pH 7.4. The synthesis of related copolymers (Inu-Spm) was performed by a two step reaction, using a method termed Enhanced Microwave Synthesis (EMS) which has the advantage, compared to conventional microwave reaction, that high amount of energy can be applied to the reaction system, by administering microwave irradiation and simultaneously controlling the temperature in the reaction vessel with cooled air. The synthesized inulin derivatives were characterized by FT-IR spectra and 1H-NMR. INU-Spm derivatives with a degree of derivatization of about 14 % mol/mol were obtained. These polycations were tested to evaluate their ability to form non covalent complexes with genetic material (polyplexes). Agarose gel retardation assays showed that the obtained copolymers are able to electrostatically interact with DNA duplex to form polyplexes at different c/p weight ratios. Moreover, light scattering studies, performed to analyze size and z-potential of polyplexes, evidenced that copolymers are able to interact with genetic material leading to the formation of nanoscaled systems. In addition, biocompatibility of polyplexes was demonstrated by performing cytotoxicity assays on a 16HBE cell line. Transfection studies, performed by using siRNA able to silence luciferase expression, demonstrate the efficiency of polyplexes to transfect the same cell line, with a reduction of luciferase expression to about 70%. These results encourage us to work with these copolymers to obtain an efficient and feasible inulin based NABD delivery system.
Keywords: microwave